Experimental evaluation of performance parameters of a domestic freezer under door opening conditions - Ipek, Mutlu; Dincer, Ibrahim (ELSEVIER, 2024)
The current study focuses on a comprehensive experimental assessment of the cooling system parameters of a domestic-type upright freezer that is equipped with shelves and test packages under periodic door opening conditions, referring to real user scenarios. The influence of varying ambient relative humidity levels as well as the load state of the cabinet are taken into account. The study reveals that both heat and moisture have a crucial effect on the average air temperature inside the cabinet, the temperature of the walls, the transient evaporation and condensation pressure behaviour of the refrigerant, as well as the compressor power, the total operation ratio of the compressor, and the overall amount of energy consumption. The specific performance experiments are conducted at 32 degrees C ambient and 35 %, 65 %, and 85 % relative humidity conditions with unloaded, halfloaded, and full-loaded cases. The obtained data and results are evaluated between frosting, influenced by altering ambient humidity levels, and cabinet load state under periodic door openings where the variation in energy consumption is clearly measured. Consequently, the amounts of frost accumulation in the cabinet under half and full loaded conditions at 32 degrees C an 85 % relative humidity conditions are observed to be about 220 g and 270 g, respectively, followed by regular door openings and closings which result in a raise in total energy consumption rate of 7.6 % and 11.2 % compared to the period before the door opening. The frost accumulation in the full loaded condition at 32 degrees C and 85 % RH is found to be 2.4 times greater than the unloaded condition with a relative humidity (RH) of 35 % whereas the energy consumption is 3.7 times higher.
Keywords: Refrigeration; Upright Freezer; Humid Air; Periodic Door Opening; Energy Consumption; System Parameters; REFRIGERATOR; ENERGY; TEMPERATURE; SIMULATION; Thermodynamics; Energy & Fuels; Engineering; Mechanics